Using Adsorption Chiller in Solar Cooling: Economic Benefits for Jordan - Saidi, Abdul Ghafour; Albaali, Ghani; Shahateet, Mohammed Issa; Mohammad, Suleiman; Daher, Zaid Omar (International Journal of Energy Economics and Policy, 2021)
Jordan has been facing a rigorous economic problem related to the high cost of energy. One of the main reasons is the cost of subsiding imported fuels to produce electricity for its domestic uses. The importation of energy represents more than 10% of its Gross Domestic Product (GDP) despite it has plentiful resources of renewable energy that can cover all its needs from electrical energy, while the national resources of energy in Jordan cover only 3-4% of the country’s energy needs. This study investigates the potential of using the technology of Cooling Air by Solar Energy (CASE) for Air-conditioning applications to minimize the consumption of energy in Jordan. The main objectives of this work are to provide an overview of different commercially available CASE technologies and analyze the economic feasibility of selected CASE technology. The study of the economic feasibility has been done on the CASE technologies used for four scenarios. Analysis of data collection and assessment of economic viability in comparison to conventional VCC was also investigated. The results showed the relevance of the economic feasibility with the cost of electricity tariff, it also showed that the use of this device is feasible at a high electricity tariff; while there is a high risk on feasibility at a low electricity tariff. Keywords: adsorption chillers; vapor compression chillers; economic feasibility JEL Classifications: C54, Q20, Q43, Q55 DOI: https://doi.org/10.32479/ijeep.11752